TINGKAT KETERGANTUNGAN KHALAYAK TERHADAP EMAIL NEWSLETTER (The Commercium, 2023)
The email newsletter is an exclusive online news subscription service that offers an easier way to receive news than reading in usual online media. Email newsletters are sent daily via email as a way for audiences to stay informed about social events in a more time efficient manner. With information sent via e-mail every day, this research has examined how the dependency dimension of the people of Surabaya City who subscribe to e-mail newsletters. This study uses the Media System Dependency Theory as a theoretical basis to see how the dependency levels depend on age and gender. This descriptive research uses the micro scope of Media System Dependency Theory which is also called Individual Media Dependency (IMD). The variables in this research are the variables of understanding goals (self & social), orientation (action & interaction), play (solitary & social) which become dependency relationships between individuals and the media that have been formed. The sample in this research were 272 individuals from the city of Surabaya who subscribed to the email newsletter service by distributing questionnaires as a way of collecting data. Pearson Product Moment is used for validity testing in this research. The reliability test in this research used Cronbach's Alpha in the scope of objectives, the understanding variable got a reliability value of 0.738, orientation got a value of 0.874, and the play got a value of 0.771. The result of this research is that the dominant dimension of dependence on the people of Surabaya City who subscribe to email newsletters is the play dimension with a percentage of 45.2%. This research is expected to be a reference and source of literacy xii regarding further audience research on email newsletters which are part of mass media communication.